2014
DOI: 10.1186/s13075-014-0486-0
|View full text |Cite
|
Sign up to set email alerts
|

Altered microbiota associated with abnormal humoral immune responses to commensal organisms in enthesitis-related arthritis

Abstract: IntroductionPrior studies have established altered microbiota and immunologic reactivity to enteric commensal organisms in inflammatory bowel disease (IBD). Since intestinal inflammation is present in a subset of patients with both pediatric and adult spondyloarthritis (SpA), we hypothesized that SpA patients may also have altered microbiota and immune responsiveness to enteric organisms.MethodsStool and blood specimens were collected from children with enthesitis-related arthritis (ERA) and non-inflammatory c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
179
8
3

Year Published

2015
2015
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(209 citation statements)
references
References 51 publications
(62 reference statements)
19
179
8
3
Order By: Relevance
“…12,13 At least 1 category of JIA has been associated with distinct intestinal microbial populations. 14 Antibiotics can alter some subjects' intestinal microbiota for $6 months. [15][16][17] Correspondingly, anaerobic antibiotic use has been associated with incident pediatric IBD.…”
Section: What's Known On This Subjectmentioning
confidence: 99%
“…12,13 At least 1 category of JIA has been associated with distinct intestinal microbial populations. 14 Antibiotics can alter some subjects' intestinal microbiota for $6 months. [15][16][17] Correspondingly, anaerobic antibiotic use has been associated with incident pediatric IBD.…”
Section: What's Known On This Subjectmentioning
confidence: 99%
“…Differences in the humoral responses to these bacteria may contribute to disease. So ERA patients may also have altered microbiota and immune responsiveness to enteric organisms which could influence gut inflammation (24), however, we do not have any data about microbiota to support this.…”
Section: Discussionmentioning
confidence: 82%
“…Stoll et al found a reduced abundance of Faecalibacterium in the stool of children with enthesitis-related JIA (24). Differences in the humoral responses to these bacteria may contribute to disease.…”
Section: Discussionmentioning
confidence: 99%
“…A similar gut microbiota profile was present in patients with inflammatory bowel disease [43]. In children with enthesitis-related arthritis (ERA) a different microbiome signature has been observed characterized by (i) less Faecalibacterium prausnitzii and lachnospiraceae family, (ii) a statistically significant increase in Bifidobacterium, and (iii) an abundance of Akkermansia muciniphila [44]. Cluster analysis revealed the presence of two clusters of ERA patients: in cluster one there were high levels of Bacteroides genus; in cluster 2 similar levels of Bacteroides genus, but abundant A. muciniphila were observed, indicating Bacteroides and A. muciniphila as associative agents in subsets of ERA patients.…”
Section: Dysbiosis In Spa Patientsmentioning
confidence: 88%